2020
DOI: 10.20944/preprints202012.0072.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constructivism Theory: The Factors Affecting Students’ Academic Performance in Higher Education

Abstract: This paper aimed to use social media impact on student studies in higher education. Apart from enjoyment and academic purposes, many educational practices and processes have been influenced by social networks. This paper highlighted the use of media tools in higher education as well as indicates out some of the factors. Moreover, through a literature review of related articles, we aim to provide insights into the impacts of a social network on educational quality, actual use of social media, and performance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…The empirical research has been used to investigate and validate the relationship between attitude components and PEOU in the IT literature. Several studies used a variety of methods for usage, and the results are consistent with those created in TAM, indicating that the two philosophies in TAM are significantly related to attitude [19,28].…”
Section: Perceived Ease Of Usesupporting
confidence: 54%
See 2 more Smart Citations
“…The empirical research has been used to investigate and validate the relationship between attitude components and PEOU in the IT literature. Several studies used a variety of methods for usage, and the results are consistent with those created in TAM, indicating that the two philosophies in TAM are significantly related to attitude [19,28].…”
Section: Perceived Ease Of Usesupporting
confidence: 54%
“…The study by [27] suggested that perceived usefulness can be determined by the adoption of the technology and students' responses to IT use and adoption [25,27,28]. Perceived usefulness refers to individuals' belief that using a certain system would improve their performance [29].…”
Section: Perceived Usefulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, including Ali et al, [7], Choi and Lam, [11] and Samsudeen and Mohamed, [12], have acknowledged the importance of e-learning in high-quality educational offerings. For example, it provided various e-learning benefits such as access from anywhere and at any time, enhanced student motivation, access to more advanced or novel learning methodologies, opportunities for self-directed education and adoption, improved ICT device arrangement, and increased maternal participation [13,14]. Empirical evidence reveals that academicians in local HEIs employ E-learning to a limited extent [15,16].…”
Section: Introductionmentioning
confidence: 99%